PENGARUH LOCUS OF CONTROL, GAYA KEPEMIMPINAN, STRES KERJA DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN - Chairul Anam; Arie Pradana; Mokhammad Wahyudi (Institut Pendidikan Tapanuli Selatan, 2022)
This study aims to analyze the effect of locus of control, leadership style, work stress and workload on employee performance. This research was conducted at PT. (HFI) Home Faucets Indonesia in Mojokerto with a sample of 34 production employees. The sampling technique was carried out on the basis of the theory from Arikunto where because the population was below 100 people, the entire population could be used as a research sample. Data were obtained from distributing questionnaires with an assessment based on the linkert scale. This type of research is quantitative using multiple linear regression analysis research methods and performs instrument testing, classical assumption testing and hypothesis testing with the SPSS version 25 application. The results of this study explain that the locus of control, leadership style, and workload variables have a significant positive effect and the work stress variable has a significant negative effect on employee performance because t-count is greater than t-table and the significance value is not greater. from 0.05, with a large t-table is 2.045 and for t-count and the results of the significance of the locus of control variable are 3.346 and 0.002, the leadership style variable is 2.881 and 0.007, the work stress variable is -3.048 and 0.002, the workload variable of 3.099 and 0.004. Based on the results of the F test, it can be concluded that there is a simultaneous influence of locus of control, leadership style, work stress and workload on employee performance with the f-count result greater than f-table (8.035 > 2.69) with a significance value of 0.000 and not to exceed 0.005. Then for the most dominant variable in this study is the locus of control. Keywords: locus of control, leadership style, work stress, workload and employee performance.